Level of Implementation of Practical Activities in Science Laboratories of Junior High School - Amrina Yusra; Indah Taqwilawaty; Yusli Kamila; Muhammad Rahmad; Roza Linda (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2026)
Practical work is an essential part of science learning because it provides students with hands-on experience to deeply understand concepts. To determine its effectiveness, a case study was conducted at SMPN 3 Siak Hulu with 60 students through questionnaires and observations. The results showed a significant gap: students' perceptions of practical work were in the "very good" category with an average score of 89.9%. However, observations indicated that hands-on laboratory practice was rarely conducted and was often replaced by teacher demonstrations. This gap is caused by various obstacles such as teacher competencies that do not match their scientific background, limited facilities, and suboptimal time management. Therefore, further research needs to focus on developing solutions such as teacher training programs, measuring the quantitative impact of minimal practical work on students' scientific skills, and expanding the study to a larger scale to validate whether this phenomenon occurs generally.